Hubungan Motivasi Belajar terhadap Hasil Belajar Mata Pelajaran Produk Kreativitas Kewirausahaan Kelas XI di SMK Semen Padang - Adlan Mughni; Nelvi Erizon (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Students’ learning outcomes are influenced by various internal and external factors, one of which is learning motivation. This study aims to analyze the relationship between learning motivation and learning outcomes in the Creative Product and Entrepreneurship (PKK) subject among 11th-grade students at SMK Semen Padang. The research employed a quantitative approach with a correlational design. The population consisted of 47 students, all of whom were included as samples using the total sampling technique. Data on learning motivation were collected through a questionnaire, while learning outcomes were obtained from official school records. Data analysis was carried out using descriptive statistics and the Pearson Product Moment correlation test. The results revealed a positive and significant relationship between learning motivation and learning outcomes (r = 0.547 > 0.288; p = 0.000 < 0.05), with a contribution of 29.9%. These findings indicate that the higher the students’ learning motivation, the better their academic performance. This study highlights the crucial role of motivation as a determinant of academic achievement and suggests that teachers should foster students’ learning enthusiasm through engaging and interactive teaching strategies.